Validity of salt intake assessment system based on a 24-h dietary recall method using a touch panel computer. (November 2014) - Satoh, Michihiro; Kato, Noriko; Hosaka, Miki; Elnagar, Noha; Tsuchihashi, Takuya; Yagi, Naoto; Ebara, Futoshi; Uchiba, Kiyoshi; Mori, Hisao; Kato, Mitsutoshi; Yamamoto, Hareaki; Yoshida, Katsumi; et al.
Abstract Background: An electronic system for salt intake assessment using a 24-h dietary recall method has been developed in Japan. We evaluated the validity of this salt intake system for assessing salt intake. Methods: We prospectively obtained data on estimated salt intake using 24-hour urinary sodium excretion (24-hUNaCl) and salt intake by the salt intake assessment system from 203 consecutive outpatients with essential hypertension (age: 67.8 ± 10.7 years; 53.7% men). Results: Mean values were 9.7 ± 2.9 g/day for 24-hUNaCl and 9.1 ± 2.9 g/day for the salt intake assessment system before corrections. The salt intake estimated by the present system was significantly correlated with 24-hUNaCl (r = 0.66, p < 0.0001). After corrections for habitual use of discretionary seasonings, habitual intake of salty foods, and physical activity, correlation coefficients between salt intake and 24-hUNaCl increased from 0.60 to 0.66 in men <65 years, from 0.80 to 0.81 in men ≥65 years, from 0.64 to 0.75 in women <65 years, and from 0.52 to 0.59 in women ≥65 years. After further correction for regional differences in average salt intake, the correlation coefficient reached 0.72 in all patients. Conclusion: After correction for dietary habits, lifestyle factors, and differences in average salt intake by region, this system may be a useful tool in Japan to encourage salt restriction in the clinical treatment of hypertension and improve public health in terms of salt restriction overall.